Correction: Sixteen-year trends in multiple lifestyle risk behaviours by socioeconomic status from 2004 to 2019 in New South Wales, Australia. - PLOS Global Public Health Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0001606.].